The Influence Of Logistic Management, Governance, And Social Responsibility On Competitiveness And Operational Performance Of Manufacturing Companies At Makassar Industrial Estate - DM, Syahrir (Politeknik APP Jakarta, 2023)
This study aimed to analyze the direct effect of logistic management, governance, and social responsibility on competitiveness and operational performance of manufacturing companies, competitiveness on operational performance of manufacturing companies, and logistic management, governance, and social responsibility through competitiveness on operational performance of manufacturing companies. The questionnaire data were analyzed using Structural Equation Model with AMOS 20. The population of this study were all manufacturing companies (127 companies) at Makassar Industrial Estate (KIMA) based on data from the Makassar City Central Bureau of Statistics in 2021. Based on the results, logistic management had positive and significant influence on operational performance with direct effect of 0.295, governance had positive and significant influence through competitiveness on operational performance with indirect effect of 0.117